Climate Change and integrated pest management - Pal, Rishi; Singh, Rajender; Prasad, C S (Indian Farming, 2017)
To establish an integrated pest management program, the following basic guidelines should be followed. Understand the biology of the crop and identify the key pests, know their biology, recognize the damage they inflict and evaluate their economic status; identify the key environmental factors that affect pest and potential pest species in the ecosystem; consider concepts, methods and materials that individually or in combination, will help to permanently suppress pest; anticipate unforeseen developments and move with caution to face the changes that can occur within it; seek the weak links in the lifecycle of the key pest species and direct control practices as narrowly as possible at these weak links; avoid broad impact on the resource ecosystem and consider and develop methods, which preserve, complement and augment the biotic and physical mortality factors that characterize the ecosystem, and diversify the ecosystem.